Universal philosophical education as an opportunity on de-ideologization of education in Poland? On the need and prospects of a new educational paradigm - in dialogue with Maciej Woźniczka - Michał Płóciennik (Jan Dlugosz University, 2022)
Maciej Woźniczka's book is quite a radical reaction to the crisis of Polish education, one of the symptoms of which is the almost total marginalization of philosophical education - optionally possible, but virtually absent in real terms. The author makes an in-depth diagnosis of the Polish education system in the context of the tension between ideas and ideologies, observing its ideologizing deformations on three planes: worldview, ideology, and politics. As a remedy for this state of affairs, he proposes the introduction of universal and obligatory philosophical education, based on a previously culturally awakened need of philosophy, from school to academic education. In the author's intention, the issue is about the necessity to change the educational paradigm towards one that corresponds to worldview pluralism, in which real and universal philosophical education should play a key role. This presentation is an attempt to look at the philosophical and educational reflection of Woźniczka, to show its strengths and weaknesses, to assess the opportunities for conceptual and practical application, to indicate internal tensions and paradoxes that govern it, and to signal development prospects. It is complemented by source intuitions about the essence of education.